2021
DOI: 10.3390/cells10020436
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Lung Injury, Repair, and Fibrosis

Abstract: Fibrosis progression in the lung commonly results in impaired functional gas exchange, respiratory failure, or even death. In addition to the aberrant activation and differentiation of lung fibroblasts, persistent alveolar injury and incomplete repair are the driving factors of lung fibrotic response. Macrophages are activated and polarized in response to lipopolysaccharide- or bleomycin-induced lung injury. The classically activated macrophage (M1) and alternatively activated macrophage (M2) have been extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(136 citation statements)
references
References 150 publications
(125 reference statements)
3
131
1
1
Order By: Relevance
“…Monocyte-derived macrophages and alveolar macrophages present antigens, phagocytose microbes, or apoptotic cells. They can be polarized into the pro-inflammatory M1 phenotype in the presence of LPS, IFN-γ, or an anti-inflammatory phenotype in IL-4 and IL-13 ( 91 ). M1 macrophages secrete TNF-α, IL-1β, and IL-6, causing tissue injury, while M2 macrophages produce IL-10 and TGF-β, associated with tissue repair and fibrosis ( 92 ).…”
Section: Immune Response To Sars-cov-2 In the Lungmentioning
confidence: 99%
“…Monocyte-derived macrophages and alveolar macrophages present antigens, phagocytose microbes, or apoptotic cells. They can be polarized into the pro-inflammatory M1 phenotype in the presence of LPS, IFN-γ, or an anti-inflammatory phenotype in IL-4 and IL-13 ( 91 ). M1 macrophages secrete TNF-α, IL-1β, and IL-6, causing tissue injury, while M2 macrophages produce IL-10 and TGF-β, associated with tissue repair and fibrosis ( 92 ).…”
Section: Immune Response To Sars-cov-2 In the Lungmentioning
confidence: 99%
“…Misharin et al revealed that the monocyte-derived alveolar macrophages (Mo-AMs) that persevere in the lung after injury resolution express higher proinflammatory and profibrotic genes than tissue-resident alveolar macrophages (TR-AMs) [ 141 ]. However, by stimulating complex microenvironment factors, both Mo-AMs and TR-AMs can be polarized into macrophage M1 or M2 phenotypes in IPF [ 142 ].…”
Section: Reactivation Of the Hh Pathway In Ipfmentioning
confidence: 99%
“…These data suggest that telomere dysfunction promotes significant infiltration or the recruitment of innate immune cells in the lungs. In addition to its role in the phagocytosis of senescent and apoptotic cells, macrophages play a promoting role in the development of pulmonary fibrosis ( 67 ). Several profibrotic genes such as arginase1 and matrix metallopeptidase 13 ( MMP13 ) were found to be upregulated in monocyte-derived macrophages in experimental pulmonary fibrosis, as well as in resident alveolar macrophages in IPF patients ( 68 ).…”
Section: The Senescence-associated Secretory Phenotype and Innate Immune Cell Infiltration Induce A Pro-fibrotic Niche In The Lungmentioning
confidence: 99%
“…Several profibrotic genes such as arginase1 and matrix metallopeptidase 13 ( MMP13 ) were found to be upregulated in monocyte-derived macrophages in experimental pulmonary fibrosis, as well as in resident alveolar macrophages in IPF patients ( 68 ). Moreover, M2 macrophages are an important regulator of pulmonary fibrosis, partially through the secretion of profibrotic interleukin-10 (IL-10) and TGF-β ( 67 ). Whether and how the recruitment of macrophages in the lungs caused by telomere dysfunction participates in pulmonary fibrosis development requires further investigation ( 69 ).…”
Section: The Senescence-associated Secretory Phenotype and Innate Immune Cell Infiltration Induce A Pro-fibrotic Niche In The Lungmentioning
confidence: 99%